Analisis Pesan Dakwah pada Akun Instagram @bagasmaulanasakti - Wawan Santoso; Fahmi Irfanudin (KOMUNIDA : Media Komunikasi dan Dakwah, 2023)
This research examines discourse on the text of the Instagram account @bagasmaulanasakti, which has 285,000 followers. The account often raises the theme of the dangers of promiscuity among teenagers. This study examines using a qualitative approach. This study aims to describe the da'wah messages of the Instagram account @bagasmaulanasakti using Teun A. Van Dijk's discourse analysis theory. This analysis focuses on text, social cognition, and social context. The results of this study indicate that the message of da'wah in the Instagram account @bagasmaulanasakti in terms of text, there is a message to stay away from dating behaviour and promiscuity. Then, regarding social cognition, the @bagasmaulanasakti account owner makes experiences among young people and current social realities as opportunities for preaching and making them da'wah content. Meanwhile, regarding the social context, there is an opinion from the community, especially young people, who think that dating is very common and natural.